Taxonomy of the Micrurus spixii species complex (Serpentes, Elapidae) - Nascimento, Lywouty R. S.; Silva, Nelson J. Jr.; Feitosa, Darlan T.; Prudente, Ana L. C. (Zootaxa, 2019)
Historically, the Micrurus spixii species complex comprises four subspecies (M. s. spixii, M. s. martiusi, M. s. obscurus, and M. s. princeps), however, recently, some authors have considered only two full species (M. spixii and M. obscurus). In this paper, we report data on meristic, morphometric, color pattern in life and after preservation, cranial osteology, and hemipenis morphology to Micrurus spixii species complex. We examined 358 specimens throughout the geographical distribution, including the type-series of all taxa. Differences in color pattern and morphology of hemipenis and skull support the existence of only two diagnosable taxa, M. spixii and M. obscurus, both considered here as a full species. We corroborate the synonymy of Micrurus s. martiusi and M. spixii based on wide overlap of meristic and morphometric characters, as well as the similarities of color pattern, hemipenis and skull characters. We can distinguished M. spixii from M. obscurus (in parenthesis) by the combination of the following characters: black cephalic cap (vs. cephalic cap absent, with red parietal region), hemipenial body with spines dispersed on the asulcate surface (vs. spines arranged in rows on the asulcate surface), capitate condition of hemipenis (vs. organ partially-capitate), narrow parietal bone with posterior angular borders (vs. enlarged parietal bone with elliptical posterior border), and relatively long venom inoculating fangs (vs. relatively short venom inoculating fangs).